Style atrybucji a reakcje na własną porażkę – projekt badań własnych - Jarmakowski, Tomasz (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The article focuses on the links between attributional style (regarded as personal trait) and succeeding, in the situation of previous failure. The attempts of research and describing these mechanisms derive from the researches of learned helplessness. To be precise from the Attributional Helplessness Model of Abramson, Seligman i Teasdale. The aim of this article is attempt to explain the lack of direct proofs between attributional styles and learned helpless arising whereas there are reliable proofs between particular attributional styles and succeeding. The article begins with survey of the most important conceptions of helplessness. Then some researches of links between succeeding and attributional styles were described. Finally the attempt of explaining the lack of direct proofs between attributional styles and learned helpless is proposed. This explanation is based on distinguishing between the situation when a lack of control is experienced (helplessness training) and the situation of experiencing single failure. The article ends with the proposal of the experiment which is planed to be a empirical verification hypothesis that individual attributional styles have relevant impact on the motivation and succeeding in the situation of previous failure.